Development and initial validation of the Support for Healthy Lifestyle (SHeL) questionnaire for adolescents. (August 2019) - Biggs, Bridget K.; Tsai Owens, Michele; Geske, Jennifer; Lebow, Jocelyn R.; Kumar, Seema; Harper, Kelly; Grothe, Karen B.; Cunningham, Megan L.; Jensen, Teresa B.; Clark, Matthew M.
Abstract: This study developed and provided initial validation for the Support for Healthy Lifestyle (SHeL), a set of scales designed to measure adolescent-perceived social support of healthy eating and physical activity. Item pool development utilized a prior focus group study of adolescents' perceptions of socially supportive behavior and a review of the literature on social support for health behavior change in adolescents. Exploratory factor analysis of the item pool completed by 220 adolescents, internal consistency estimates, and expert review of items and consensus resulted in 9 scales for the SHeL: Family Healthy Eating Support, Family Physical Activity Support, Family Hypocritical Control, Peer Health Eating Support, Peer Physical Activity Support, Peer Undermining, Professional Healthy Eating Support, Professional Physical Activity Support, and Professional General Support. Scale internal reliability estimates were α = 0.73–0.96. Supporting construct validity, the SHeL showed a pattern of stronger correlations between measures of the same source (parent/peer) and target behavior (healthy eating/physical activity) and stronger correlations with corresponding Sallis scales vis-à-vis other Sallis scales, with exceptions related to peer support for healthy eating. Divergent validity was somewhat limited, including in two instances, the SHeL scale was more strongly correlated with another SHeL scale. Supporting criterion validity, often the SHeL scales were correlated with related health behaviors. This study provided important psychometric information for a new measurement of social support for health behavior for adolescents. Further research with larger, more diverse, and treatment-seeking populations is needed to provide further validation of the SHeL and to begin to establish normative scores. Highlights: The new Support for Healthy Lifestyle (SHeL) assesses adolescent-perceived support for healthy weight management behaviors. Domains of family support/influence are Healthy Eating, Physical Activity, and Hypocritical Control. Domains of peer support/influence are Healthy Eating, Physical Activity, and Undermining. Domains of professional support/influence are Healthy Eating, Physical Activity, and General Support. The study provides information about the SHeL scales' internal consistency, construct validity, and criterion validity.